EVOLUTION OF DENTAL HYGIENE STUDENTS' PERSPECTIVES ON ORAL HEALTH IN PRECLINICAL AND CLINICAL YEARS OF MEDICAL EDUCATION - A.V. BLINOVA; E.V. BITYUKOVA; YU.S. SMIRNOVA (Паёми Сино)
Objective: To assess the evolution of dental hygiene students' perspectives on oral health in the 2nd, 4th, and 5th years of students at the Faculty of Dentistry at Tver State Medical University in Tver, Russia.